Sistem Penentuan Rumah Tangga Miskin Di Kota Bengkulu Menggunakan Metode SMART - Khairullah, Khairullah; Marhalim, Marhalim; Juhardi, Ujang; Wahyu Febriansyah, Eky (Jurnal Teknologi Sistem Informasi dan Sistem Komputer TGD, 2023)
Poverty is one of the problems that seems to continue to arise in this country's problems. The Social Service is one of the government agencies engaged in the social sector which carries out data collection activities and determines poor households in the city of Bengkulu. The problem in this study is that the determination of poor households is still done manually so that they are prone to errors or human errors in the process. In this research a software system for determining poor households has been created so that it can be a tool for the Bengkulu City Social Service in determining household categories in the Bengkulu City community. In this study, the SMART method was used because the SMART method is multi-criteria that supports many criteria in determining decision-making and does not affect the weighting calculation if there are additional or reduced alternatives because each alternative assessment does not depend on one another. Apart from that, to determine the grouping of poor household categories, where from the calculation results of the SMART method, the process of determining the final stage of determining poor households will be carried out. In discussing this research regarding the application of the SMART method, it can provide the final result in the form of determining household categories in each family data.